Cyclical Stretching Induces Excess Intracellular Ca2+ Influx in Human Keloid-Derived Fibroblasts In Vitro. Issue 2 (9th November 2022) - Mineda, Kazuhide; Sato, Katsuya; Nakahara, Tasuku; Minami, Kazuyuki; Yamashita, Yutaro; Ishida, Soshi; Abe, Yoshiro; Hashimoto, Ichiro
Abstract : Background: The incidence of keloids is higher in the case of darker skin. It is more common in the parts exposed to stretching (thorax, abdomen, and joints). Cyclical stretching reportedly induced each Ca 2+ spike through differential mechanosensitive channels in human synovial and dermal fibroblasts. Therefore, the authors hypothesized that cyclical stretching also induces a specific Ca 2+ spike in keloid-derived fibroblasts. Methods: This in vitro study compared the intracellular calcium dynamics induced by cyclical stretching between control (human dermal fibroblasts) and keloid (human keloid-derived fibroblasts) groups. Each group was exposed to two-dimensional stretch using an originally developed stretch microdevice. Intracellular Ca 2+ was observed for 5 minutes, including 30 seconds of baseline, under a fluorescent confocal laser microscope. The intracellular Ca 2+ concentration was evaluated every 0.5 second using the fluorescence intensity ratio. A positive cellular response was defined as a rise of the ratio by greater than or equal to 20%. The normal response cutoff value was determined by receiver operating characteristic analysis. Results: The keloid groups were significantly more responsive than the control groups (15.7% versus 8.2%; P = 0.029). In the cellular response-positive cells, the keloid groups reached significantly higher intracellular Ca 2+ concentration peaks than the control groups (2.20 versus 1.26; P = 0.0022). The cutoff value was 1.77, and 10.4% of the keloid-derived fibroblasts exhibited a hyper-Ca 2+ spike above the normal range. Conclusions: Keloid-derived fibroblasts with a hyper-Ca 2+ spike might constitute a keloid-specific subpopulation. Hereafter, the authors will study whether the normalization of excessive intracellular Ca 2+ concentration leads to keloid treatment in vivo. Clinical Relevance Statement: This study result provided a clue to the onset mechanism of keloids, which the authors hope will lead to the development of new therapy in the future.